Ethical issues of organ donation after cardiac death - O. N. Reznik; A. E. Skvortcov; O. V. Popova (Вестник трансплантологии и искусственных органов)
There is renewal of interests to the organs that could be obtained from asystolic donors. Our goal was to identify ethical issues raised by attempts of classification  and terms such kind of organ donors depended on time and place of cardiac arrest.  Based only on the reasoning of medical experts group these principles going to be  routine State policy. That followed by erased roles of physicians and misleading the  meaning or organ transplant program. From our point of view there should be clear  opposite position between death and life in order to initiate organ procurement  activity. That is possible only in case of artificial blood supply for preserving  transplant-to-be-organs after relevant time between cardiac arrest and start of such kind of perfusion procedure.